Risk Behaviours Associated with Dating and Relationship Violence among 11–16 Year Olds in Wales: Results from the 2019 Student Health and Wellbeing Survey - Couturiaux, Danielle V. R. (Int J Environ Res Public Health, 2021)
(1) Background: This study examines the associations between risk behaviours and adolescent emotional and physical dating and relationship violence (DRV) victimisation and perpetration, and how these vary by gender. The risk behaviours explored include bullying, cyberbullying, sexting, alcohol, and cannabis use; (2) Methods: Cross-sectional self-report data from the School Health Research Network (SHRN) 2019 Student Health Wellbeing (SHW) survey of 48,397 students aged 11–16 from 149 schools across Wales were analysed using single and multiple-behaviour logistic regression models to explore the associations between each risk behaviour and emotional and physical DRV victimisation and perpetration; (3) Results: Bivariate analyses revealed a statistically significant association between DRV and all risk behaviours. In multivariate analyses, students who reported bullying, cyberbullying, sexting, and substance use, compared to those that had not, had significantly higher odds of experiencing and perpetrating emotional and physical DRV; and (4) Conclusions: Future studies on DRV should consider a mixed-methods approach to explore the context in which DRV and risk behaviours interrelate. Results from this study indicate the possibility that prevention and intervention programmes in school settings that seek to develop healthy school environments and peer-to-peer relationships, could inadvertently reduce the occurrence of future DRV and associated risk behaviours.